Utilization of Antenatal Care Service in Tamang Community, Nepal - Aryal , Nava Raj; Timalsina , Suresh (Educational Journal, 2025)
This study investigates the utilization of antenatal care (ANC) services among Tamang women in Helambu Rural Municipality, Sindhupalchok District, Nepal. Using a descriptive and quantitative research design, data were collected from 168 married women aged 15–49 years who had at least one child under five years of age through structured interviews. Main purpose of this study is to identify the antenatal care situation as well as to examine the relationship between educational status and antenatal care services of Tamang women. Findings revealed that 85.1% of respondents received ANC services during pregnancy, while 14.9% did not. The majority (53.8%) obtained services from government hospitals, and 68.5% were assisted by doctors or nurses. However, only 16.1% of women met the World Health Organization’s recommended four or more ANC visits. Educational status of both women and their husbands significantly influenced ANC utilization, with higher education levels associated with greater use of antenatal care services. Economic hardship (48%) and lack of awareness (40%) were major barriers to service uptake. The study concludes that enhancing health education, addressing socio-economic barriers, and improving accessibility to maternal care facilities are vital to increase ANC utilization among the Tamang community